(untitled) (AGROINNOVATSIYА, 2023)
The article describes the effect of mineral and organic fertilizers and phosphogypsum on changes in soil fertility and ammonium and nitrate nitrogen levels due to application of irrigated barren-meadow soils of Surkhandarya region. According to the results of the study, taking into account the state of soil reclamation, the use of 30 t ha-1 of cattle manure and 2 and 4 t ha-1 of FG on the background of mineral fertilizers changed the soil fertility and agrochemical properties in a positive direction, and it was observed that the amount of nitrogen in the form of ammonium and nitrate in the soil increased compared to the control option. In N250P175K125 background, 30 t ha-1 of manure and 2 and 4 t ha-1 of FG were used (9;10), the amount of nitrogen in ammonium form was 34,3 and 35,2 mg/kg in the 0-30 cm layer of the soil, respectively, compared to the control option. compared to 19,3 and 20,2 mg/kg, and the amount of nitrate nitrogen was 37,7 and 38,8 mg/kg, which was 22,3 and 23,4 mg/kg more than the control version.